Hubungan antara Motivasi Kerja dan Pemahaman dengan Evaluasi Program Bimbingan dan Konseling - Indrajaya, Ary Bima; Sugiyo, Sugiyo (Indonesian Journal of Guidance and Counseling: Theory and Application, 2014)
Based on un executed in implementing guidance and counseling program evaluation and less interested in learning to implement guidance and counseling program evaluation, this study aims to: (1) determine the relationship between work motivation and the execution of guidance and counseling evaluation, (2) determine the relationship between counselor understanding of guidance and counseling evaluation program with the execution of guidance and counseling evaluation, (3) determine the relationship between motivation and counselor understanding of guidance and counseling evaluation program  with the execution of guidance and counseling evaluation. The population in this study was the whole high school counselors in Temanggung Regency. Methods of data collection in this study using the scale of work motivation, comprehension test counseling and guidance program evaluation and program evaluation questionnaire implementation guidance and counseling. The data analysis technique used was the regression analysis. The results of this study indicated that there was a positive and significant relationship between motivation and understanding of program evaluation guidance counselors and counseling with the evaluation of guidance and counseling in SMA as Temanggung.